2000
DOI: 10.1074/jbc.m000238200
|View full text |Cite
|
Sign up to set email alerts
|

Two Different Signal Transduction Pathways Are Implicated in the Regulation of Initiation Factor 2B Activity in Insulin-like Growth Factor-1-stimulated Neuronal Cells

Abstract: Eukaryotic initiation factor eIF-2B plays an important role in translation regulation and has been suggested to be implicated in the increased protein synthesis promoted in response to growth factors. We have used primary cultured neurons to delineate the signaling pathways by which insulin-like growth factor-1 (IGF-1), which plays a critical role in the survival of neuronal cells, promotes eIF-2B and protein synthesis activation. Treatment of cortical neurons with IGF-1 (100 ng/ml) for 30 min stimulates [ 3 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 40 publications
4
51
1
Order By: Relevance
“…19) In some systems, these processes were found to be independently activated and equally important for angiogenic activity, 29) whereas in others, PI3K or ERK signaling played more dominant roles. 30) Our data showed that KRGE activated the MEK/ERK1/2, PI3K/Akt, and eNOS/NOS pathways, which were critically involved in its angiogenic activity.…”
Section: Discussionmentioning
confidence: 99%
“…19) In some systems, these processes were found to be independently activated and equally important for angiogenic activity, 29) whereas in others, PI3K or ERK signaling played more dominant roles. 30) Our data showed that KRGE activated the MEK/ERK1/2, PI3K/Akt, and eNOS/NOS pathways, which were critically involved in its angiogenic activity.…”
Section: Discussionmentioning
confidence: 99%
“…PI 3-kinase has been identified as the major transducer of the IGF-IR signal in other cellular systems, and its activity was shown to be critical for IGF-I-induced cell survival, mitogenesis, and transcriptional and translational regulation of protein synthesis (16,(47)(48)(49)(50)(51)(52). In some systems, these processes were found to be equally dependent on ERK signaling (47,50), whereas in others, the PI 3-kinase pathway or ERK signaling played more dominant roles (48,53).…”
Section: Changes In Signaling In Response To High Dose Igf-i Evidencmentioning
confidence: 99%
“…In some systems, these processes were found to be equally dependent on ERK signaling (47,50), whereas in others, the PI 3-kinase pathway or ERK signaling played more dominant roles (48,53). The degree to which different cells utilize these pathways to convey IGF-IR signals may be cell context-dependent and could be determined, among others, by the levels and accessibility of downstream substrates such as insulin receptor substrate-1 or Shc (40,53,54) and by the repertoires and activation levels of other receptor tyrosine kinasess, such as the epidermal growth factor receptor, expressed by the cells (56).…”
Section: Changes In Signaling In Response To High Dose Igf-i Evidencmentioning
confidence: 99%
“…At the cellular level IGF-I can increase neuronal survival and protect neurons against the toxicity of amyloid peptides [15][16][17]. Through activation of the phosphatidylinositol 3 kinase (PI3K)/Akt pathway IGF-I also inhibits glycogen synthetase kinase (GSK)-3β, a Tau-kinase thought to be involved in hyperphosphorylation of tau, the major component of neurofibrillary tangles [18,19]. In addition, through its ability to modulate insulin sensitivity, IGF-I, which may also participate in the loss of neuronal sensitivity to insulin recently reported in Alzheimer's patients [8,20,21].…”
Section: Igf-i In Alzheimer's Diseasementioning
confidence: 99%